Nationwide molecular survey of Dirofilaria immitis and Dirofilaria repens in companion dogs and cats, United States of America - Rachel Smith; Daniel Felipe Barrantes Murillo; Kelly Chenoweth; Subarna Barua; Patrick John Kelly; Lindsay Starkey; Byron Blagburn; Theresa Wood; Chengming Wang (Parasites & Vectors, 2022)
Abstract Background Heartworms, Dirofilaria immitis, are known to be widespread in dogs and cats in the USA, but there have been no country-wide prevalence studies performed to date. There have also been no large-scale studies to determine whether the closely related species, Dirofilaria repens, occurs in the USA. Methods To provide this large-scale data, we examined whole blood samples (n = 2334) submitted from around the USA to the Molecular Diagnostic Laboratory at Auburn University between 2016 and 2022. Quantitative PCRs for D. immitis (targeting 16S rRNA) and D. repens (targeting cytochrome c oxidase subunit 1 gene) were performed to determine the presence of Dirofilaria DNA. DNA sequencing was performed to confirm the results. Results Dirofilaria immitis DNA was found in 6.3% (68/1080) of the dogs from 17/39 states, and 0.3% (4/1254) of the cats from 4/42 states. None of the dogs or cats were positive for D. repens. The average 16S rRNA copy number of D. immitis in the dogs was 1,809,604 in 200 µl whole blood, while only a single copy was found in each of the four D. immitis-positive cats. The prevalence of D. immitis in dogs of different ages, sexes, and breeds did not differ significantly, but the prevalence in Southern states (7.5%, 60/803) was significantly higher than in the Western (1.7%, 1/58), Midwest (3.3%, 4/120), and Northeastern states (3.1%, 3/98) (P < 0.05). Dogs positive for D. immitis were identified in each study year (2016: 4.2%, 2/48; 2017: 9.8%, 4/41; 2018: 5.1%, 8/156; 2019: 4.9%, 15/306; 2020: 9.8%, 26/265; 2021: 4.9%, 13/264). Interestingly, dogs infected with Hepatozoon spp. (11.8%, 37/313) were significantly more likely to also be positive for D. immitis than dogs without evidence of Hepatozoon infection (3.9%, 30/760) (P < 0.0001). Conclusions To our knowledge, this is the first nationwide molecular survey of Dirofilaria spp. in dogs and cats in the USA, and the largest molecular survey of canine and feline dirofilariosis worldwide. Further studies are warranted to combine PCR with standard heartworm diagnostics to better understand the prevalence of Dirofilaria spp. and aid in determining the risks posed to dogs and cats in the USA. Graphical Abstract